Causal effect of polyunsaturated fatty acids on bone mineral density and fracture - Tao, Sha-Sha; Wang, Peng; Wang, Xin-Yi; Yin, Kang-Jia; Yang, Xiao-Ke; Wang, Zhi-Xin; Wang, De-Guang; Pan, Hai-Feng (Frontiers in Nutrition, 2022)
Background Polyunsaturated fatty acids (PUFAs) are closely related to osteoporosis. To test their causal relationship, we conducted a Mendelian randomization (MR) analysis. Methods We analyzed the causal relationship between four PUFAs measures, n-3 PUFAs (n-3), n-6 PUFAs (n-6), the ratio of n-3 PUFAs to total fatty acids (n-3 pct), and the ratio of n-6 PUFAs to n-3 PUFAs (n-6 to n-3), and five measures of osteoporosis, including estimated bone mineral density (eBMD), forearm (FA) BMD, femoral neck (FN) BMD, lumbar spine (LS) BMD, and fracture, using two-sample MR analysis. In order to verify the direct effect between PUFAs and BMD, we chose interleukin-6 (IL-6), tumor necrosis factor-β (TNF-β), and bone morphogenetic proteins 7 (BMP-7), three markers or cytokines strongly related to BMD, as possible confounding factors, and analyzed the possible causal relationships between them and PUFAs or BMD by MR. Inverse variance weighting (IVW), MR-Egger, weighted and weighted median were conducted. MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) and MR-Egger regression methods were used to evaluate the potential pleiotropy of instrumental variables (IVs) and outliers were identified by MR-PRESSO. Cochran’s Q statistic was used to detect the heterogeneity among IVs. Leave-one-out sensitivity analysis was used to find SNPs that have a significant impact on the results. All results were corrected by the Bonferroni correction. Results The IVW results showed that n-3 PUFAs (OR = 1.030, 95% CI: 1.013, 1.047, P = 0.001) and n-6 PUFAs (OR = 1.053, 95% CI: 1.034, 1.072, P < 0.001) were positively correlated with eBMD, while n-6 to n-3 (OR = 0.947, 95% CI: 0.924, 0.970, P < 0.001) were negatively correlated with eBMD. These casual relationships still existed after Bonferroni correction. There were positive effects of n-3 PUFAs on FA BMD (OR = 1.090, 95% CI: 1.011, 1.176, P = 0.025) and LS BMD (OR = 1.056, 95% CI: 1.011, 1.104, P = 0.014), n-3 pct on eBMD (OR = 1.028, 95% CI: 1.002, 1.055, P = 0.035) and FA BMD (OR = 1.090, 95% CI: 1.011, 1.174, P = 0.025), n-6 to n-3 on LS BMD (OR = 1.071, 95% CI: 1.021, 1.124, P = 0.005); negative effects of n-3 pct on fracture (OR = 0.953, 95% CI: 0.918, 0.988, P = 0.009) and n-6 to n-3 on FA BMD (OR = 0.910, 95% CI: 0.837, 0.988, P = 0.025). However, these causal effects all disappeared after Bonferroni correction (all P > 0.0025). None of IL-6, TNF-β, and BMP-7 had a causal effect on PUFA and BMD simultaneously (all P > 0.05). Conclusion Evidence from this MR study supports the genetically predicted causal effects of n-3, n-6, n-3 pct, and n-6 to n-3 on eBMD. In addition, n-3 not only associate with FA BMD and LS BMD through its own level and n-6 to n-3, but also link to fracture through n-3 pct.